Debt, Taxes and Corporate Restructuring - Shoven, John B.; Waldfogel, Joel (Rowman & Littlefield Publishers, 2012)
The boom in corporate restructuring, accompanied by large increases in debt finance, was one of the most important developments in the U.S. economy in the 1980s. Financial and tax specialists analyze how the U.S. tax system-especially in its bias toward debt financing-has affected corporate financial decisions and influenced the recent wave of corporate restructuring. The authors evaluate the hypothesis that the rise in the cost of capital during the 1980s helped stimulate the surge in corporate takeovers. They analyze the effect that changes in tax laws and in the volume of government debt have had on corporate financial decisions. The authors examine how recent financial innovations have blurred the distinction between debt and equity finance.